The Effect of Self-Efficacy and Problem-Solving Skills on Social Skills through On-The-Job Training in Indonesian Aviation Cadets - ., Parjan; ., Ekohariadi; Suhartini, Ratna; Anistyasari , Yeni (Journal of Ecohumanism, 2025)
Cadets of the Airport Electrical Engineering Study Program at Aviation Polytechnic face challenges in maximizing On-the-Job Training (OJT). Self-efficacy and problem-solving skills are believed to influence OJT success and also support the development of social skills which are crucial in the dynamic airport work environment. This study aims to analyze the influence of self-efficacy and problem-solving skills on the social skills of cadets in the Airport Electrical Engineering study program, with OJT as a mediating variable. Self-efficacy and problem-solving skills are believed to be important in influencing cadets' performance when facing complex practical tasks at airports. The method used was Structural Equation Modeling (SEM) to evaluate the direct and indirect relationships between these variables. Data were collected through questionnaires from cadets who had undergone OJT. The results showed that self-efficacy and problem-solving skills had a positive significant effect on OJT performance, which in turn significantly affected social skills achievement. Strong self-efficacy increases cadets' confidence in communicating and collaborating with colleagues, while problem-solving skills help them overcome challenges and conflicts more effectively. The conclusion of this study suggests that increased self-efficacy and problem-solving skills can strengthen social skills through practical experience gained during OJT, which is critical for success in an aviation work environment.